2008
DOI: 10.1111/j.1099-1123.2008.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Industry Specialists More Efficient and Effective in Performing Analytical Procedures? A Multi‐stage Analysis

Abstract: A substantial body of audit research has shown that auditor specialisation through training and experience in one main industry improves auditor judgements. However, because this research examines only one or two audit processes in isolation, it has not been possible to identify whether these improvements lead to gains over an entire task. Further, the comparison of auditors with very different industry specialisations has not allowed these studies to identify incremental gains of specialisation over task and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The development of industry specialization/expertise is a strategy adopted by the largest accounting firms (Hogan & Jeter, 1999). Consistent with learning curve theory, industry specialist auditors work more efficiently on individual tasks when working within their area of expertise (Moroney, 2007) and are generally more efficient than nonspecialists (Green, 2008). Most research using audit fees has shown that efficiencies may occur with increased industry specialization (Cahan et al, 2011; DeFond et al, 2000).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
“…The development of industry specialization/expertise is a strategy adopted by the largest accounting firms (Hogan & Jeter, 1999). Consistent with learning curve theory, industry specialist auditors work more efficiently on individual tasks when working within their area of expertise (Moroney, 2007) and are generally more efficient than nonspecialists (Green, 2008). Most research using audit fees has shown that efficiencies may occur with increased industry specialization (Cahan et al, 2011; DeFond et al, 2000).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 95%
“…Finally, an auditor's industry expertise has been found to be positively related to the quality of audits. Auditors with industry specialization have been found to outperform non-specialists in error detection (Owhoso et al 2002), in performing analytical procedures (Wright and Wright 1997;Green 2008), in assessing components of audit risks (Taylor 2000;Low 2004;Hammersley 2006;Maroney and Simnett 2009), and in disclosing internal control deficiencies (Rose- Green et al 2011;Stephens 2011).…”
Section: Knowledge and Expertisementioning
confidence: 99%
“…S. -Vietnam Security Relations since Normalization: 1995-2008(Saarbrucken, Germany: VDM Verlag Dr Muller, 2011…”
Section: About the Authorsmentioning
confidence: 99%